Pengaruh Kepemimpinan Kepala Sekolah Dan Beban Kerja Guru Terhadap Mutu Sekolah Dasar Negeri Di Kecamatan Susukan Kabupaten Semarang - Sutinem Sutinem (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2022)
The research of problems are: 1) is there any influence of principal's leadership on school quality in SD Negeri Susukan District, Semarang Regency?, 2) Is there any effect of teacher workload on school quality in SD Negeri Susukan District, Semarang Regency?, 3) Is there any Is there an influence of the principal's leadership and the workload of teachers together on the quality of schools in SD Negeri Susukan District, Semarang Regency?. This type of research is descriptive correlation study or descriptive association study, which is to examine the relationship between two things, two or more variables. The populations in this research were all elementary school teachers in Susukan sub-district and it totals are 223 people. The sample of the research was 140 peoples. The sampling of research used simple random sampling technique. The data collection method used is a questionnaire. Analysis of the data used descriptive analysis, test requirements and hypothesis testing which includes simple linear regression analysis and multiple regression analysis. To analyze the data, the SPSS for windows version 25 program was used. The results of this research are: 1) leadership has an effect on school quality. The results of the partial test obtained that the t-count value of the influence of the principal's leadership on school quality was 13,419 while the t table (a = 0.05, dk = n – 2, dk = 140 – 2 = 138) was 1.655. The calculation results obtained t count (13.419) > t table (1.655) and a significance value of 0.001. Because the significance value is known to be less than 0.05 (<5%), then Ho is rejected and H1 is accepted. 2) Workload Affects School Quality. The results of the partial test obtained that the t-count value of the effect of workload on school quality was 4.763 while t-table (a = 0.05, dk = n – 2, dk = 140 – 2 = 138) was 1.655. The calculation results obtained t count (4.763) > t table (1.655) and a significance value of 0.001. The result of the significance value is known to be less than 0.05 (<5%), then Ho is rejected and H2 is accepted. 3) leadership and workload together on school quality. The feasibility test of the model can be seen with the results of the F test. The feasibility test of the model is used to test whether the linear model is correct or not, then it is seen by comparing the probabilities of the results of the F test calculation. If the probability value is < 0.05 then the model in the regression is fit models. Suggestions in this research are suggested that the principal should be able to provide considerations and policies in school programs, and supervise school services and follow up on complaints, suggestions, criticisms and aspirations of all school staff so that the school's vision and mission can be achieved.